Catalytic asymmetric synthesis of (−)-E-δ-viniferin via an intramolecular C–H insertion of diaryldiazomethane using Rh2(S-TFPTTL)4. Issue 29 (15th July 2015) - Natori, Yoshihiro; Ito, Motoki; Anada, Masahiro; Nambu, Hisanori; Hashimoto, Shunichi
Graphical abstract: Abstract: An asymmetric synthesis of (−)- E -δ-viniferin, a trans -resveratrol dimer natural product containing a dihydrobenzofuran ring, has been achieved by exploiting a Rh(II)-catalyzed intramolecular C–H insertion reaction of a diaryldiazomethane derivative as a key step. The C–H insertion under catalysis by dirhodium(II) tetrakis[ N -tetrafluorophthaloyl-( S )- tert -leucinate], Rh2 ( S -TFPTTL)4, provided the 2, 3-diaryl-2, 3-dihydrobenzofuran core structure with perfect cis diastereoselectivity and 96% ee.